Imbue problem-solving skills in law school curriculums to off-set adversarial ‘hired-gun’ mind-set - Ali Mohamed, Ashgar Ali; Ahmad, Muhamad Hassan (2019)
It is undeniable that the alternative mode of dispute resolution such as mediation and conciliation is in most circumstances able to improve the strain relationship between the disputants. Adjudication before the court would be as the last resort only when the parties are unable to resolve the dispute amicably. To this end, members of the legal fraternity have to place clients’ interests above their own, and have to discard their litigation mind-set and promote, for example, mediation, although it may lead to less revenue. Individual lawyers who earn a living from the fee he/she charges the client, may not be receptive of mediation because there would be a lesser role for them if mediation is implemented. The adversarial ‘hired-gun’ mind-set has to be corrected. Hence, this paper proposes that the law school curriculum must move away from the adversarial nature of teaching and training lawyers by integrating alternative dispute resolution system. The law school curriculum must stress on lawyers’ problem-solving (instead of problem-making) skills, i.e. emphasis on dispute settlement as opposed to litigation. The law students ought to be taught the basic concept of alternative dispute resolution at the earliest stage of their legal education. The mediation/conciliation skills should be integrated into substantive law subjects and to be reflected in the curriculum, teaching and examination. By having such a programme, it is hoped that the would-be lawyers should be imbued with a mind-set of problem-solving and not just acquiring the skills of advocacy in litigation.